2020
DOI: 10.1016/j.ebr.2020.100383
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of all causes and sudden unexplained death in epilepsy (SUDEP) in a cohort of 235 persons living with epilepsy in Rwanda using WHO Verbal Autopsy Questionnaire

Abstract: Introduction Mortality in persons living with epilepsy (PwE) is 1.6–9.3-fold higher than in the general population. Mortality from definite/probable Sudden Unexpected Death in EPilepsy (SUDEP) is estimated at 1.2 per 1000 person-years. We report mortality and SUDEP rate in a cohort of Rwandan PwE. Methods PwE presenting for a first visit at the Ndera epilepsy center between January and June 2016 were followed-up prospectively. For PwE who did not attend their follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In this way, by monitoring all patients defined as "at risk, " we could highlight the pathophysiological mechanisms of SUDEP that today are unclear. The interaction between the various systems of the human body in the determination of sudden cardiac death in epileptic patients could be investigated by encouraging machine learning (67,68). The second use of deep learning is closely related to the first: through machine learning resulting from research, extrapolated data can be applied for prevention purposes.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, by monitoring all patients defined as "at risk, " we could highlight the pathophysiological mechanisms of SUDEP that today are unclear. The interaction between the various systems of the human body in the determination of sudden cardiac death in epileptic patients could be investigated by encouraging machine learning (67,68). The second use of deep learning is closely related to the first: through machine learning resulting from research, extrapolated data can be applied for prevention purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors thank Prof Josef Finsterer for his concerns and comments expressed in his letter to the editor on the article of mortality and sudden unexpected death in epilepsy (SUDEP) [1] . The authors considered all deaths identified in a cohort of 235 persons living with epilepsy (PWE) and administered the World Health Organization verbal autopsy age-specific questionnaire (WHO-VAQ) [2] .…”
mentioning
confidence: 99%
“…We read with interest the work of Sebera et al, about a study of mortality from sudden unexpected death in epilepsy (SUDEP) in 235 epilepsy patients from Rwanda [1] . Probable SUDEP was diagnosed in 3/235 patients of whom none underwent autopsy.…”
mentioning
confidence: 99%